Indonesian Chinese in the Netherlands and the legacies of violence in colonial and post-colonial Indonesia - van der Meer, Alexander; Eickhoff, Martijn (Wacana, Journal of the Humanities of Indonesia, 2017)
After Indonesian independence in 1945, thousands of Indonesian Chinese repatriated to the Netherlands, the former colonizer. As opposed to other repatriates from Indonesia, who organized themselves into pressure groups and fought for a place in the national memory culture, the Indonesian Chinese in the Netherlands only formed strict socio-cultural associations and have generally stayed clear of identity politics. Usually, this divergence is attributed to the smooth integration and socio-economic success of the latter group, as well as to Chinese values, such as conflict avoidance. This article adds to this explanation by positing that this phenomenon has also been induced by the legacy of anti-Chinese violence in colonial and post-colonial Indonesia: respectively, Dutch discomfort to acknowledge the violent and discriminatory elements of its own colonial history, as well as a fear of offending the Indonesian government. Consequently, many Indonesian Chinese in the Netherlands have engaged in some form of public self-silencing.